2022
DOI: 10.1002/slct.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐Based Materials for Water Purification

Abstract: Cellulose is a linear syndiotactic homopolymer, made up of glucose units designated as D‐anhydroglucopyranose units (AGU). The glucose units are connected with each other by b‐(l‐4)‐glycosidic linkage to form a dimeric structure known as cellobiose. These units are assembled into microfibils in a heirarchial manner with excellent strength and stiffness. The properties of cellulose can be further enhanced by either surface functionalization or by converting it to nano form. Nanocellulosic materials are non‐toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…The ionic power of the solution rises with the concentration of KCl, and Sr (II) adsorption in carboxymethylcellulose declines. This indicates that ions' adsorption is also affected by ionic force from the medium (Jain et al 2022).…”
Section: Discussionmentioning
confidence: 92%
“…The ionic power of the solution rises with the concentration of KCl, and Sr (II) adsorption in carboxymethylcellulose declines. This indicates that ions' adsorption is also affected by ionic force from the medium (Jain et al 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Literatures report that adding succinic acid groups to cellulose nanocrystals (CNCs) dramatically improved their ability to bind Pb 2+ and Cd 2+ out of aqueous solutions [ [63] , [64] , [65] , [66] , [67] , [68] ]. Additionally, heavy metal ions, organic solvents, and crude oil can all be removed using cellulose-based nanocomposites as adsorbents [ 69 , 70 ]. It has been reported that silane-treated, cross-linked polyvinyl alcohol (PVA) and cellulose nanofibril (CNF) hybrid organic aerogels exhibit excellent absorption for heavy metal ions (such as Pb 2+ and Hg 2+ ) and crude oil [ 71 ].…”
Section: Nanoparticle Utilization In the Oil And Gas Industrymentioning
confidence: 99%
“…Cellulose-based adsorbents have been widely used in water treatment, and their modification methods, properties, and application have been reviewed in literature [ 23 , 57 , 58 , 59 ]. However, the sorptive removal of Cr(VI) by cellulose-based adsorbents has not been systematically reviewed.…”
Section: Polymers Used For Cr(vi) Removalmentioning
confidence: 99%